Case Report: Novel compound heterozygous variants in CHRNA1 gene leading to lethal multiple pterygium syndrome: A case report - Jianlong Zhuang; Junyu Wang; Qi Luo; Shuhong Zeng; Yu’e Chen; Yuying Jiang; Xinying Chen; Yuanbai Wang; Yingjun Xie; Yingjun Xie; Gaoxiong Wang; Chunnuan Chen (Frontiers in Genetics, 2022)
Background: Lethal multiple pterygium syndrome (LMPS) is a rare autosomal recessive inherited disorder typically characterized by intrauterine growth retardation, multiple pterygia, and flexion contractures.Case presentation: We herein report a Chinese case with a history of three adverse pregnancies demonstrating the same ultrasonic phenotypes, including increased nuchal translucency, edema, fetal neck cystoma, reduced movement, joint contractures, and other congenital features. Whole-exome sequencing (WES) revealed novel compound heterozygous variants in the CHRNA1 gene NM_000079.4: c.[1128delG (p.Pro377LeufsTer10)]; [505T>C (p.Trp169Arg)] in the recruited individual, and subsequent familial segregation showed that both parents transmitted their respective mutation.Conclusion: For the first time, we identified an association between the CHRNA1 gene and the recurrent lethal multiple pterygium syndrome (LMPS) in a Chinese family. This finding may also enrich the mutation spectrum of the CHRNA1 gene and promote the applications of WES technology in etiologic diagnosis of ultrasound anomalies in prenatal examination.